O processo de gestão do design no arranjo produtivo do vestuário de Colatina: uma investigação a partir do capital social. - Puppo, Jaquelini Loureiro Del (2006)
This study entails the four following issues: modernity, fashion consumption, fashion design, as well as its use in the production process. The approach is wide and engages the understanding of the local development, seen through the concept of social cap